Family support in practice: voices from the field. Issue 5 (3rd September 2018) - Dolan, Patrick; Shannon, Mary; Smyth, Berni
ABSTRACT: This paper revisits core family support messages for social work practice in working with children and families, linking to findings from high-profile child protection cases in the UK and the Republic of Ireland. Drawing on a comparative study where these identified practice messages were explored through the lens of testimony of family support workers in the UK and Ireland, these core messages are examined. Operating with hard-to-engage children and parents, we hear how families and family support worker colleagues now view the core functions of child and family work across both jurisdictions (Ireland and England). The authors argue that by naming a more detailed set of practices that are deemed as most useful by families, based on the benefits and challenges of intensive family support work, key messages arise that have major resonance for social work and multiagency practice into the future. A basic message from this study is that valuable lessons on engagement and intervention with families can be drawn for professionals by examining the practice elements of this group of paraprofessionals in the child and family arena. This paper adds to debates on the role of support and intervention in social work and family support work.